Immunoexpression of Nestin and Ki-67 in Astrocytoma in a Single Tertiary Health Care Centre - Prih Bashir; Noshaba Rahat; Humera Shahzad; Asma Jalbani; Farah Siraj; Zumrud Momin (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: To evaluate the prognostic significance of Nestin and Ki-67 expression in Astrocytoma across different grades. METHODOLOGY: A retrospective cross-sectional analysis was conducted at the Histology Department, Basic Medical Sciences Institute, JPMC Karachi, between October 2019 and September 2022. In this study, Nestin and KI-67 immunohistochemistry expression was assessed in 60 Astrocytoma, and its expression was seen with different degrees of Astrocytoma. RESULTS: Nestin positivity was found in 86.7% of cases of Astrocytoma. The immune-reactive score for Nestin staining in different stages of Astrocytoma was shown to have a significantly significant P-value. 41.7% of cases of Astrocytoma were found to have a KI-67 labeling index; all high-grade Astrocytoma had a high labeling index of Ki-67. It was demonstrated that the immune-reactive score for Ki-67 staining at various phases of Astrocytoma had a statistically significant P-value. CONCLUSION: We discovered that Nestin and Ki-67 were expressed in Astrocytoma and that the expression of both immune markers rose with tumor grade. Nestin and Ki-67 serve as a helpful marker for assessing the Astrocytoma's prognosis. These findings may be used to determine the best course of action for Astrocytoma therapy.